2021
DOI: 10.1029/2021wr030238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Reclamation on Fresh Groundwater Lenses in Oceanic Islands: Laboratory and Numerical Validation

Abstract: There are approximately 425 atolls in the world (Falkland, 1992) and most of them belong to Small Island Developing States (SIDS) in the Indian and Pacific Oceans. About 65 million people live in these SIDS (UN-OHRLLS, 2015). When precipitation recharge across an oceanic island is sufficient, a fresh groundwater lens (or freshwater lens) develops above the denser saline groundwater derived from the sea, which is a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Sheng et al concluded that the lower hydraulic conductivity of filling materials, higher reclamation length, and thickness could result in a larger volume of fresh groundwater. 29 There is currently limited study on the effects of land reclamation on island groundwater systems on time scales. In the study of atoll island groundwater systems, these islands are often represented as symmetrical models with homogeneous aquifer features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheng et al concluded that the lower hydraulic conductivity of filling materials, higher reclamation length, and thickness could result in a larger volume of fresh groundwater. 29 There is currently limited study on the effects of land reclamation on island groundwater systems on time scales. In the study of atoll island groundwater systems, these islands are often represented as symmetrical models with homogeneous aquifer features.…”
Section: Introductionmentioning
confidence: 99%
“…After the investigation of the impact of filling materials and reclamation scale on FGL. Sheng et al concluded that the lower hydraulic conductivity of filling materials, higher reclamation length, and thickness could result in a larger volume of fresh groundwater …”
Section: Introductionmentioning
confidence: 99%
“…Recently, fresh groundwater lenses (FGL) in coastal reclamation islands have received more attention. Sheng et al (2020) and Sheng et al (2021) respectively, used a numerical model (a numerical model of variable density flow and solute transport) and a combination of various methods (sandtank experiments, sharp-interface analytical solutions, and numerical modeling) to study the influence of land reclamation on FGL and GWL in the South China Sea. However, the numerical model is limited by field data, and the combination of various methods ignores the influence of tidal fluctuation which affects the vertical flow and the release or compression of water [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al (2020) and Sheng et al (2021) respectively, used a numerical model (a numerical model of variable density flow and solute transport) and a combination of various methods (sandtank experiments, sharp-interface analytical solutions, and numerical modeling) to study the influence of land reclamation on FGL and GWL in the South China Sea. However, the numerical model is limited by field data, and the combination of various methods ignores the influence of tidal fluctuation which affects the vertical flow and the release or compression of water [24,25]. Ling et al (2021) used a three-dimensional numerical model of variable density flow and solute transport to study the impact of island urbanization on FGL on a small coral island in Sansha City, Hainan Province, China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation